2017
DOI: 10.5812/mejrh.44743
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity; Knowledge, Attitudes, and Practices of Students Living in Semnan University of Medical Sciences Dormitories in Semnan, Iran

Abstract: Introduction: Physical activity (PA) plays an important role in health promotion as well as disease prevention, especially among young adults. The aim of this study was to determine the knowledge, attitudes, and practices towards PA among medical sciences students living in university dormitories in Semnan, Iran. Methods: In a cross-sectional study, 421 students living in the dormitories of Semnan University of Medical Sciences, Semnan, Iran, were randomly included to the study. Students' knowledge of physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our findings concur with that of similar studies done in Semnan and Delhi. [7,11] The results of this study indicated that overall, medical students possess a reasonable level of knowledge about the importance of physical activity for maintaining good health. This is an encouraging finding, as medical students are expected to be well-informed about health benefits of physical activity due to their academic background.…”
Section: Discussionmentioning
confidence: 73%
“…Our findings concur with that of similar studies done in Semnan and Delhi. [7,11] The results of this study indicated that overall, medical students possess a reasonable level of knowledge about the importance of physical activity for maintaining good health. This is an encouraging finding, as medical students are expected to be well-informed about health benefits of physical activity due to their academic background.…”
Section: Discussionmentioning
confidence: 73%